Knowledge and Awareness about Identification of Domestic Violence, Abuse and Neglect of Victim among Dentists - Sunitha S; Vidya G Doddawad; Sushma R (Institute of Medico-legal Publications Pvt Ltd, 2021)
Domestic violence is an age-old social evil which remains hidden from the eyes of the society for long.The incidence of domestic violence (DV) is at epidemic proportions of violence, abuse and neglect of anyindividual have a significant impact on the social system. Majority of the studies report violent and abusiveinjuries involve the head and neck region but many times dentists fail to report abuse. The various reasonscould include loss of patients, economic loss and fear of dealing caregivers or of getting involved. Aboveall these, the majorly lack of sufficient knowledge about identification uncertainty of diagnosis and agencieswhere to report. The purpose of this paper is to assess the knowledge regarding identification of domesticviolence, abuse and neglect and reporting agencies of maltreatment.Aim & Objective: The aim of the present study is to assess knowledge and create awareness regardingidentification of domestic violence, abuse and neglect and reporting agencies of maltreatment among dentistsof Mysuru city of India.Method: A self-administered, structured questionnaire written in English given to the dentists who givetheir consent.Results: 91.7% (n=100) of the participants had heard about Domestic Violence, neglect and abuse and73%(n=67) had come across victims of Domestic violence, neglect and abuse. Among them, 9.2% (n=10)had come across them frequently and 32 (29.8%) occasionally.51 respondents said that the domestic violence victims are adult females, elderly female patients (16.6%)followed by children between 12 to 15 years of age (13.7%)Conclusion: Many dentists will come across and identify the victims in their practice, but only few dentistswill make an attempt to report. The main reason being lack of knowledge and proper training. Thus, there is aneed for all of us to get trained in this aspect. Recognizing reporting the violence is everyone’s responsibility